Workplace Peer Effects in Fertility Decisions - Maria De Paola; Roberto Nisticò; Vincenzo Scoppa (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper examines the impact of co-workers' fertility on individual fertility decisions. Using matched employer-employee data from Italian social security records (2016–2020), we estimate how fertility among co-workers of similar age and occupation affects the individual likelihood of having a child. We exploit variation introduced by the 2015 Jobs Act, which reduced fertility among workers hired under weaker employment protection. Focusing on workers hired before the reform and using the share of colleagues hired after the reform as an instrument for peer fertility, we find that a one-percentage-point increase in peer fertility raises individual fertility by 0.4 percentage points (a 10% increase). Heterogeneity analysis suggests that while social influence and social norms are key mechanisms, information sharing and career concerns, particularly among women, tend to moderate the response. Our findings highlight how changes in employment protection may have unintended fertility spillovers through workplace social interactions.
Keywords: C3; J13; J65; J41; M51; 330; career concerns; EPL; fertility; social learning; social norms; workplace